Analysis of Workload and Physical Work Environment in Increasing Employee Job Satisfaction in Convection RR83 Production - Dina Novitasari; Mochamad Vrans Romi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Human resources are the company's most valuable asset and must be considered for their welfare. Based on the results of an interview with one of the employees, dissatisfaction stems from two main factors. First, dissatisfaction with an unbalanced workload, especially when there is a surge in production demand. Second, the uncomfortable physical working environment conditions caused by the poorly organized layout of the production room, accompanied by limited room space. This study aims to determine the workload and physical work environment in increasing employee job satisfaction in RR83 Production convection. The research method uses a qualitative approach with the data collection methods used, namely observation, interviews, documentation, and literature research. The research population used social situations, in this study, namely the activities of RR83 Production convection employees. The sample used was purposive sampling, which is an employee of the tailoring section. The data collection instrument in this study is the researcher himself. Test the validity of the data using triangulation. The results of the study show that workload has an impact on increasing job satisfaction. In addition, the physical work environment also has an impact on increasing job satisfaction. Overall, workload and physical work environment have an impact on increasing job satisfaction.